Supplementation with D carvone Induces Cytotoxicity and Mitochondrial Mediated Apoptosis in Human Colon Cancer Cell Lines HT 29 and SW480 - Nalini, Namasivayam (International Journal of Pharmaceutical & Biological Archive, 2013)
Supplementation with D carvone Induces Cytotoxicity and Mitochondrial Mediated Apoptosis in Human Colon Cancer Cell Lines HT 29 and SW480